Agreement between the force platform method and the combined method measurements of power output during the loaded countermovement jump - Mundy, P. D.; Lake, J. P.; Carden, P. J.C.; Smith, N. A.; Lauder, M. A. (Sports Biomechanics, 2016)
There are two perceived criterion methods for measuring power output during the loaded countermovement jump (CMJ): the force platform method and the combined method (force platform+optoelectronic motion capture system). Therefore, the primary aim of the present study was to assess agreement between the force platform method and the combined method measurements of peak power and mean power output during the CMJ across a spectrum of loads. Forty resistance-trained team sport athletes performed maximal effort CMJ with additional loads of 0 (body mass only), 25, 50, 75 and 100% of body mass (BM). Bias was present for peak velocity, mean velocity, peak power and mean power at all loads investigated, and present for mean force up to 75% of BM. Peak velocity, mean velocity, peak power and mean power 95% ratio limits of agreement were clinically unacceptable at all loads investigated. The 95% ratio limits of agreement were widest at 0% of BM and decreased linearly as load increased. Therefore, the force platform method and the combined method cannot be used interchangeably for measuring power output during the loaded CMJ. As such, if power output is to be meaningfully investigated, a standardised method must be adopted.